2007
DOI: 10.1007/s12038-007-0111-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity of carbohydrate-binding sites in β-prism fold lectins: occurrence and possible evolutionary implications

Abstract: The beta-prism II fold lectins of known structure, all from monocots, invariably have three carbohydrate-binding sites in each subunit/domain. Until recently, beta-prism I fold lectins of known structure were all from dicots and they exhibited one carbohydrate-binding site per subunit/domain. However, the recently determined structure of the beta-prism fold I lectin from banana, a monocot, has two very similar carbohydrate-binding sites. This prompted a detailed analysis of all the sequences appropriate for tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…BP1 proteins also bind carbohydrates with up to three binding sites, and a common origin of BP1 and BP2 has been discussed without clear conclusion [42]. The large distance between BP1 and BP2 proteins in our cluster map (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…BP1 proteins also bind carbohydrates with up to three binding sites, and a common origin of BP1 and BP2 has been discussed without clear conclusion [42]. The large distance between BP1 and BP2 proteins in our cluster map (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…However, only one of the keys has a binding site in the archeal lectin domains, as in the case of artocarpin. It has been suggested in the case of β‐prism fold lectins also that the fold could have resulted from successive gene duplication, fusion and divergent evolution of a primitive Greek key based carbohydrate binding motif . It has been further suggested that there is a correlation between the average sequence identity among the three Greek keys and the number of binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…The dual preference of VCC for complex N-linked glycans (25) and for O-linked sugars in asialofetuin might be a reflection of the multiple carbohydrate-binding specificities exhibited by ␤-prism fold lectins (34,35).…”
Section: C-terminal ␤-Prism Lectin Fold and Binding To Asialofetuin-mentioning
confidence: 99%